PERAN DIASPORA INDONESIA-FILIPINA SELATAN (DIFS) DALAM PEMBERDAYAAN EKONOMI WARGA KETURUNAN INDONESIA PEMUKIM (WKIP) DI FILIPINA SELATAN - Putri, Rara Gusnita (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2017)
Until now Indonesian citizen who live in the border area between Indonesia and the Philippines especially in the southern Philippines are in social inequality and economic marginalization. The marginalization is come from the different attitude of the public and even the Philippine government against Indonesian citizen in Southern Mindanao, Philippines. This study is aimed at analyzing on how Diaspora Indonesia Southern Philippines role in the economic empowerment of the Indonesian citizen in Southern Mindanao, Philippines. The study was conducted by using a qualitative approach and the deep investigation towards government programs through a case study analysis and using structuralism as a theoretical guidance. Data from this study consisted of secondary data through literature study and analysis of documents and primary data obtained from resource person who are relevant and reliable as well as through field research. The results of this study indicate that the Diaspora Indonesia Southern Philippines program in efforts towards economic empowerment in Southern Mindanao, Philippines. In this case the increase in skills in order to increase productivity Indonesian citizen in Southern Mindanao, Philippines. Field findings indicate that the program Diaspora Indonesia Southern Philippines, Public and Private Partnership encourages Indonesian citizen to be separated from social inequality and economic marginalization that exist. In this case the increase in skills in order to increase productivity Indonesian citizen in Southern Mindanao, Philippines.